PENINGKATAN MINAT BACA TULIS AL-QUR’AN MELALUI METODE KOOPERATIF MODEL TGT (TEAMS GAME TOURNAMENT) KELAS 7C DI SMPN 1 KARAWANG BARAT: PENINGKATAN MINAT BACA TULIS AL-QUR’AN MELALUI METODE KOOPERATIF MODEL TGT (TEAMS GAME TOURNAMENT) KELAS 7C DI SMPN 1 KARAWANG BARAT - Rahmawati, Mira; Juanita Diana; Nur Alim; Nur Aini Farida; M. Makbul (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2024)
Teams Games Tournament (TGT) is a learning model that combines learning with games. Students will be divided into study groups, so that each group will compete with each other to get points that are superior to other groups. This research was conducted using a qualitative method which is a type of Classroom Action Research (PTK). The research was conducted at SMPN 1 West Karawang class 7C with a total of 40 students. The purpose of the study was to determine the effect of TGT on students' interest in reading and writing the Qur'an. The results showed that in cycle 1, group 1 was obtained with the largest average score, which was 70% while the other groups were still classified as low. While in cycle 2, all groups experienced an increase in average. This shows that the TGT learning mode can form students who are more enthusiastic in learning, so as to increase students' interest in reading the Qur'an.